Capital inflows and economic growth: does the role of institutions matter? - Slesman, Ly; Baharumshah, Ahmad Zubaidi; Wohar, Mark E. (International Institute of Finance and Economics, 2015)
Recent evidence shows that institutions figure prominently in explaining the ‘Lucas paradox’. Using a threshold regression model, we extend this evidence to a situation where institutions index the relationship between foreign capital inflows and economic growth. We find strong and robust evidence that portfolio equity (including foreign direct investment) and debt inflows have positive effects on growth only in countries with high‐quality institutions. Countries that fall below the threshold level of institutional quality record either insignificant or negative effects. This paper provides a possible explanation on the so‐called Lucas paradox.